(untitled) (European Journal of Pure and Applied Mathematics, 2026)
Delineating the tactical approach of the “ELiminating Et Choice Translating REality” (ELECTRE) technique and the “Technique for Order Preference by Similarity to Ideal Solution” (TOPSIS) for multi-attribute group decision-making in terms of complex spherical fuzzy soft sets is the focus of this study. The decision-making effectiveness and ranking quality of the proposed methods are greatly improved by the distinctive, pioneering, and significant structure of proposed set. This makes it an outstanding and proficient approach for addressing multi-attribute group decision-making. This is a result of the fact that suggested work is able to provide a comprehensive performance with a useful and more sophisticated competence method. In addition to the presented approach, a number of non-fundamental features of the complex spherical fuzzy soft weighted averaging operators are investigated. These qualities include shift invariance, homogene- ity, linearity, and additive properties. The individual views are validated into an acceptable form by the use of the this operator, and the aggregated opinions are further analyzed by the suggested complex spherical fuzzy soft ELECTRE I technique and the CSFS-TOPSIS technique. Normalized Euclidean distances of complex spherical fuzzy soft numbers are also taken into account as part of the approach that has been developed. A decision graph is formed on the basis of an aggregated outranking matrix to get the solutions that are outranked and the optimal option. This article offers a supplemental strategy at the very end of the process, which aims to provide a linear rank- ing order for the many possibilities. An example case study taken from the medical field helps to illustrate the adaptability and practicability of the strategy that is introduced.